Coprecipitation technique to prepare BaNb2O6 - Natarajan, N; Samuel, V; Pasricha, R; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
A mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and niobium ions as barium oxalate and niobium hydroxide under basic conditions. This precursor on calcination at 750degreesC yielded BaNb2O6 ceramics. This is a much lower temperature as compared to that prepared by traditional solid-state method (1000degreesC), as reported for the formation of BaNb2O6. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ammonia; Ceramics; Electron microscopy; niobium oxide; Oxides

DNA and PNA as templates for building nanoassemblies via electrostatic complexation with gold nanoparticles - Gourishankar, A; Shukla, S; Pasricha, R; Sastry, M; Ganesh, Krishna N. (Current Applied Physics, 2005)
Organisation of nanoparticles on structurally well-defined templates is a first step towards creating nanomachines. In this respect, nucleic acids are ideal structural templates and a variety of secondary structures realizable from DNA/RNA - e.g., duplexes, hairpins, triplexes, cruciforms, tetraplexes can be exploited to engineer nanoparticle organization at will. We have used oligonucleotides and their analogues such as phosphorothioates and peptide nucleic acids to electrostatically encapsulate cationic-capped gold nanoparticles. This article describes synthesis and characterization of DNA/PNA-gold nanoparticle composites using TEM and UV-T-m techniques. These types of assemblies may have potential for creating nanowires and lithographic circuits. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: DNA; DNA-gold nanoparticle interactions; nanoassemblies; PNA

Preparation of nanocrystalline ferroelectric BaNb(2)O6 by citrate gel method - Gaikwad, S. P.; Samuel, V; Pasricha, R; Ravi, V (Bulletin of Materials Science, 2005)
A gel was formed when a aqueous solution of BaCl2, NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600 degrees C yielded the nano crystallites of BaNb2O6, as confirmed by X-ray diffraction study (XRD). This is a much lower temperature as compared to that prepared by traditional solid state method (1000 degrees C) as reported for the formation of BaNb2O6. Transmission electron microscopic. (TEM) investigations revealed that the average particle size is 50 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1000. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides

Preparation of nanocrystalline ferroelectric CaBi2Ta2O9 by the urea method - Gaikwad, S. P.; Pasricha, R; Ravi, V (Ceramics International, 2005)
A precipitate was formed when a aqueous solution of CaCl2, BiCl3, TaF5 and urea in stoichiometric ratio (total metal cations to urea ratio is 5) is heated on a water bath. This precipitate on decomposition at 600 degrees C yielded the nanocrystallites of ternary oxide CaBi2Ta2O9 (CBT) as confirmed by X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). Ferroelectric hysteresis loop parameters such as remnant polarization (P-r) and coercive field (E-C) were also determined. TEM investigations revealed that the average particle size of the polycrystalline powder is 70 nm. The room temperature dielectric constant was found to be 110. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders : chemical preparation

Preparation of nanocrystalline ferroelectric CaBi2TaO9 by citrate gel method - Gaikwad, S. P.; Pasricha, R; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
A gel was formed when an aqueous solution of CaCl2, BiCl3, TaF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600degreesC yielded the nano-crystallites of ternary oxide, CaBi2Ta2O9 (CBT) as confirmed by X-ray diffraction study (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). Ferroelectric hysteresis loop parameters such as remnant polarization (P-r) and coercive field (E-C) are also determined. TEM investigations revealed that the average particle size of the polycrystalline powder is 40 nm. The room temperature dielectric constant was found to be 90. (C) 2004 Elsevier B.V All rights reserved.
Keywords: Bismuth; diffraction; Electron microscopy

Preparation of nanocrystalline MgNb2O6 by citrate gel method - Pasricha, R; Ravi, V (Materials Letters, 2005)
A gel was formed when a aqueous solution of Mg(NO3)(2), NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C produced the fine crystallites of ternary oxide, MgNb2O6 (MN). The formation of MN phase and lattice parameters were determined by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Citrate gel; Electron microscopy; magnesium niobate; powders; X-ray diffraction

Synthesis of CdS and alloyed CdMnS nanocrystals using aqueous foams - Kumar, P. Senthil; Kasture, Manasi; Raghavan, U; Pasricha, R; Sastry, M (Journal of Nanoscience and Nanotechnology, 2005)
Certain surfactant-stabilized aqueous foams provide a potentially efficient and simple chemical route for the synthesis of various nanomaterials with controllable structure, size, and shape. In the present work, a one-step process for the synthesis of CdS and Cdl(1-x)Mn(x)S (0 < x < 10) nanocrystals has been described. Aqueous CdCl2 and the aerosol-OT solutions are homogeneously mixed together and thereafter, nitrogen is bubbled through this solution to produce stable aqueous foam. After drainage of the foam, the freestanding dry foam consisting of cadmium cations electrostatically complexed with the anionic aerosol-OT molecules at the liquid-gas interface is treated with H2S vapor. The foam turns yellowish-orange and collapses, in the process yielding CdS nanoclusters of variable morphology. This morphology variation is appropriately attributed to growth of the CdS as well as alloyed Cd1-xMnxS nanoparticles in different regions of the foam contributing to the varying topological structure. Optical absorption spectra of both CdS and Cd1-xMnxS nanoparticles clearly show a well-defined exciton absorption feature around 450 nm due to quantum confinement effects. The interesting band edge emission characteristics of these AOT-capped CdS and Cd1-xMnxS nanoparticles produced in the foam are discussed with respect to their size and shape. Particular interest in the present novel aqueous foam approach arises due to the fact that the cubic zincblende CdS and alloyed Cd1-xMnxS nanocrystals could easily be obtained even under ambient experimental conditions itself.
Keywords: absorption and fluorescence; aerosol-OT; alloyed CdMnS nanocrystals; aqueous foams; CdS nanoclusters; quantum confinement; zincblende

Synthesis of nanocrystalline rutile - Samuel, V; Pasricha, R; Ravi, V (Ceramics International, 2005)
Nanocrystalline titanium dioxide (TiO2) in the rutile phase has been obtained by homogeneous precipitation using urea and TiOCl2. A mixture of urea and TiOCl2 is heated on a hot water bath at 65-75 degrees C to precipitate rutile powders. X-ray diffraction (XRD) studies on these oven-dried powders indicated the formation of single-phase rutile. Raman scattering experiments were also performed to confirm the formation of the rutile phase. Transmission electron microscopy (TEM) investigations revealed the average particle size of these powders to be 40 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical preparation; Electron microscopy; powders; TiO2; X-ray methods

Synthesis of Sr0.5Ba0.5Nb2O6 by citrate gel method - Pasricha, R; Ravi, V (Materials Chemistry and Physics, 2005)
A gel was formed when an aqueous solution of BaCl2, SrCl2, NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C yielded the nanocrystallites of ternary oxide, Sr0.5Ba0.5Nb2O6 (SBN) as confirmed by X-ray diffraction study (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at I kHz is 1000. The ferroelectric hysteresis loop parameters of these samples were also studied by a home built Sawyer-Tower circuit. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides

Transmetalation reaction between hydrophobic silver nanoparticles and aqueous chloroaurate ions at the air - Water interface - Pasricha, R; Swami, A; Sastry, M (Journal of Physical Chemistry B, 2005)
The transmetalation reaction between a sacrificial nanoparticle and more noble metal ions in solution has emerged as a novel method for creating unique hollow and bimetallic nanostructures. In this report, we investigate the possibility of carrying out the transmetalation reaction between hydrophobic silver nanoparticles assembled and constrained at the air-water interface and subphase gold ions. We observe that facile reduction of the subphase gold ions by the sacrificial silver nanoparticles occurs resulting in the formation of elongated gold nanostructures that appear to cross-link the sacrificial silver particles. This transmetalation reaction may be modulated by the insertion of an electrostatic barrier in the form of an ionizable lipid monolayer between the silver nanoparticles and the aqueous gold ions that impacts the gold nanoparticle assembly. Transmetalation reactions between nanoparticles constrained into a close-packed structure and appropriate metal ions could lead to a new strategy for metallic cross-linking of nanoparticles and generation of coatings with promising optoelectonic behavior.